Understanding Spatial House Price Dynamics in a Housing Boom - Leo Kaas; Georgi Kocharkov; Nicolas Syrichas (CESifo GmbH, 2024)
We examine the evolution of spatial house price dispersion during Germany's recent housing boom. Using a dataset of sales listings, we find that house price dispersion has significantly increased, which is driven entirely by rising price variation across postal codes. We show that both price divergence across labor market regions and widening spatial price variation within these regions are important factors for this trend. We propose and estimate a directed search model of the housing market to understand the driving forces of rising spatial price dispersion, highlighting the role of housing supply, housing demand and frictions in the matching process between buyers and sellers. While both shifts in housing supply and housing demand matter for overall price increases and for regional divergence, we find that variation in housing demand is the primary factor contributing to the widening spatial dispersion within labor market regions.
Keywords: D83; R21; R31; 330; house price dispersion; spatial housing markets; search frictions in housing markets